PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP TAX AVOIDANCE - Muliana, Sitti; Supryadi, Supryadi (Patria Artha Journal of Accounting dan Financial Reporting, 2023)
The purpose of this study was to determine and analyze the effect Profitabilitas and Leverage of the Tax Avoidance. The study was conducted on the building construction company and listed on Indonesia Stock Exchange for the period 2015 – 2020. A total of 37 samples were selected using the purposive sampling method. Source of data in this study are secondary data in the form of the firm’s financial statements. The data analysis method used is multiple regression analysis. The results of this study showed that partially pofitabilitas has positif effect on tax avoidance, while leverage has not effect on tax avoidance. Simultaneously, profitabilitas and leverage has an effect on tax avoidance.